Implementation of Risk Management for the Management of Third-Party Infrastructure, Facilities, and Public Utilities (PSU) Obligations - Mikhael Sakharov Simarmataa; Machmudin Eka Prasetya (Eduvest - Journal of Universal Studies, 2025)
Third-party Infrastructure, Facilities and Public Utilities (PSU) liabilities arise from Space Utilisation Permits received by third parties to utilise land they own. Many liabilities for Space Utilization Permits have not been submitted, even though the Space Utilization Permit has expired, and the land is being utilized by third parties, who should be using public facilities. Risk management is made so that the risks in managing these liabilities can be reduced to an acceptable level, and the objectives in managing third-party PSU liabilities can be achieved. In implementing risk management, this study uses the ISO 31000: 2018 framework to guide the risk management process. The process starts from identification, analysis, evaluation, and risk treatment. The method used in risk evaluation is assessing the likelihood and impact. Based on the results of the research, 24 risk events were obtained, which were then analysed and evaluated, showing three risk events in the very high category, four risk events in the high category, 8 risk events in the medium category, and nine risk events in the low and very low categories. For risk events with medium to very high categories, this research provides suggestions for risk mitigation actions that the DKI Jakarta Provincial Government can take to reduce the occurrence of these risks.